Risk communication: lessons from an ethnographic, pragmatic, and Canadian regulatory perspective - Bhuller, Yadvinder; Trevithick-Sutton, Colleen C. (Frontiers in Communication, 2024)
In a regulatory context, it is important to understand how effective risk communication fits into the overall risk assessment, management, and decision-making process. This includes recognizing the intersections between risk analysis and the 3Ps: policy, politics, and publics, and understanding the barriers to effective communication. Risk communication is especially challenging when it requires the audience to follow and act on authoritative information or advice. Risk communicators must factor attributes such as risk perception, tolerance, and behaviors, and tailor the delivery of messages to diverse audiences. This paper captures the discourse from an intradepartmental workshop on risk communication with participants from Health Canada and the Public Health Agency of Canada. The workshop provided an opportunity to discuss and share references to existing frameworks, pertinent documents, and examples of effective risk communication strategies based on the authors' ethnographic and pragmatic experiences. The workshop aimed to strengthen risk communication by better understanding the value in collaborating with interdisciplinary teams, applying a systems thinking lens, and finding opportunities to experiment and evaluate risk communication strategies for regulatory purposes.